Effect Of Weather Risk On Assets And Labour Allocation Decisions Among Smallholder Farm Households In Developing Countries: Evidence From Burkina Faso - Gansonre, S. (University of Ghana, 2018)
Around the developing world, poverty remains an overwhelming rural issue. Rural dwellers rely heavily on agricultural activities and related assets as main source of livelihoods. They also have widely differing capacities to combine off-farm activities in their income generation process. However, diversification makes households better-off only if it implies increased investment in high return portfolios. An important concern is that high yielding investments are either high risk or exhibit severe entry barriers. In the absence of risk markets, liquidity constrained households may pursue low risk investments to self-insure against income volatility which may create poverty. This study explores how this risk induced behaviour may lead to poverty among smallholder farm households in Burkina Faso by analysing the effect of rainfall risk on their asset holdings and attitudes towards low risk off-farm activities. Two theoretical models are developed using stochastic dynamic programming methods to highlight the mechanisms through which risk implies resource diversion towards less risk but also less profitable agricultural investments. Optimal allocation decisions appear to be determined by the relative profitability of available options which is function of the risk. This implies that consumption smoothing is indirectly pursued by smoothing returns to assets and activities. It is also shown that the household more readily enters off-farm activity as volatility of return to farming increases. Empirical analysis uses a two-year panel data collected in 2010 and 2011 in Burkina Faso. Results suggest that households accumulate liquid assets as a long-term strategy to deal with anticipated rainfall outcomes. Liquidity constraints also contribute to shape the composition of households’ portfolio as well as transaction costs. In addition to these factors, off-farm labour supply is influenced by rainfall uncertainty and rainfall shocks. However, the data suggest that productive farm assets (farm equipment and draught animals), and farming in general, have better returns than less productive liquid assets (livestock, poultry and grain stocks) and off-farm activities as the latter are less attractive to wealthier households. The tendency to accumulate increased level of liquid unproductive assets or work more off-farm will therefore result in lower income paths which may explain why poverty persists. Enabling households to accumulate more farm productive assets and work more on farm is necessary to boosting their income generation capacities. This implies addressing the rainfall risk they face. In the short-term, policies may promote groundwater pump irrigation and fodder crop cultivation to mitigate yield volatility and improve returns from livestock breeding. In the medium term, the development of a rural credit market will encourage high yielding investment directly by enabling households to overcome liquidity constraints and indirectly by enhancing ex-post risk management. Regulatory policies that improve returns to riskless options (liquid assets and off-farm work) are needed. This includes provision of veterinary care, establishment of guaranteed minimum wage and efforts to reduce transaction costs. In the long-term, a structural transformation of the farming system that lowers the reliance on rainfed farming through the development of irrigation schemes and the development of agricultural insurance and irrigation schemes may be pursued.
Thesis (PhD)
Keywords: Weather Risk; Assets; Labour Allocation Decisions; Smallholder; Farm Households; Developing Countries; Burkina Faso; Africa